Life satisfaction and its influencing factors of middle-aged and elderly stroke patients in China: a national cross-sectional survey. Issue 8 (3rd August 2022) - Liu, Ying; Liu, Jieyu; Zhou, Shangcheng; Xu, Xingying; Cheng, Yu; Yi, Ying; Zou, Guanyang
Abstract : Objectives: This study reports the life satisfaction of middle-aged and elderly patients who had a stroke in China, and explores its association with patients' sociodemographic characteristics, health status, lifestyles and family relationship. Design: Cross-sectional survey. Setting and participants: The samples of this study were selected from the data of China Health and Retirement Longitudinal Study (CHARLS) in 2018, which covered 28 provinces, 150 countries/districts and 450 village/urban communities. 1154 patients who had a stroke aged 45 and over were included in this study as qualified samples. Outcome measures: Descriptive analysis was used to report sociodemographic characteristics, health status, lifestyles, family relationship and life satisfaction of middle-aged and elderly patients who had a stroke. χ 2 analysis and binary logistic regression were used to analyse the factors influencing the life satisfaction of the patients who had a stroke. Results: Overall, 83.1% of patients who had a stroke were satisfied with their lives, although only 8.7% rated their own health as being good. Patients who had a stroke who were male, elderly, married, living with their spouses and having a pension were more likely to report satisfaction with life (p<0.05). Self-rated health, health satisfaction, chronic lung disease, fall, pain, ability to work and family relationships were also significantly associated with life satisfaction (p<0.05). Patients who drank alcohol (86.8% vs 81.7%, p=0.041), had physical activity (84.4% vs 75.6%, p=0.004) and had social activity (85.3% vs 80.8%, p=0.041) were more satisfied with their lives than those who did not. Multivariable analysis confirmed that age, health satisfaction, physical pain, working ability, relationships with spouse and with children had significant effects on life satisfaction of patients who had a stroke (p<0.05). Conclusions: Our study indicates the importance of improving the overall health of patients who had a stroke and mediating factors, such as pain management, and work ability, spouse and children relationship in improving the life satisfaction of patients in the poststroke rehabilitation.